Habitat suitability modeling for anoa (Bubalus spp.) in Mountain Sojol Nature Reserve, Central Sulawesi, Indonesia - ONGKY ONGKY; ABDUL HARIS MUSTARI; LILIK BUDI PRASETYO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ongky, Mustari AH, Prasetyo LB. 2025. Habitat suitability modeling for anoa (Bubalus spp.) in Mountain Sojol Nature Reserve, Central Sulawesi, Indonesia. Biodiversitas 26: 1395-1404. Anoa are large mammal endemic to Sulawesi Island, Indonesia, inhabiting lowland to mountainous areas. The quality, quantity, and distance of the habitat from human activities mainly influence habitat selection. Mountain Sojol Nature Reserve in Central Sulawesi is a vital refuge for this endemic species. However, Mountain Sojol Nature Reserve faces pressure from human activities, such as agriculture and hunting, which can lead to human-wildlife conflict. Spatial approaches are essential and can be used to monitor conservation areas effectively. Therefore, it is necessary to understand species' spatial distribution and habitat. The study was conducted from September to December 2023. Anoa Habitat Suitability Model (HSM) using the MaxEnt algorithm, based on anoa presence data from 2019 to 2024 and six environmental variables: elevation, land cover, forest canopy density, distance from rivers, distance from roads, and distance from agricultural fields. The habitat suitability analysis showed that approximately 40,135.83 ha (58.5%) of the total area is suitable for anoa. Among the environmental variables, elevation was the most significant contributor (36.5%), followed by distance from rivers (25.5%), distance from roads (19.3%), and distance from agricultural fields (17.7%) in modeling anoa habitat suitability in Mountain Sojol Nature Reserve. Finally, Conservation efforts are essential, especially in habitat management and stricter monitoring in areas with suitable habitat for anoa, to prevent forest conversion and poaching. Conservation education is also needed to raise public awareness of the importance of this species in the area.